Senzeni Na? Honouring The Role of Liberation Songs As A Powerful Tool That Gave A Voice- And So Power- To South Africa's Oppressed Majority In The Struggle To End Apartheid - O'Connell, Siona (University of Pretoria, 2021)
Dissertation (MSoSci)--University of Pretoria, 2020.